2017
DOI: 10.3390/ma10050504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emulsified Asphalt on the Mechanical Property and Microstructure of Cement-Stabilized Gravel under Freezing and Thawing Cycle Conditions

Abstract: Properties of cement-stabilized gravel modified by emulsified asphalt under freezing and thawing cycle conditions were investigated by adjusting the dosage of cement. Mercury intrusion porosimetry (MIP) and Scanning electron microscopy (SEM) were introduced to analyze the influential mechanism. The results indicate that cement emulsified asphalt stabilized gravel with 5 wt % of cement performed well in both mechanics and frost-resistance. Although the addition of emulsified asphalt would lead to a partial decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…A similar tendency was observed by Meidani et al [11,16,17], and it can be explained by the large size and the high strength of the gravels. Thelarger the size of the gravels, the less contacting points in the CGM at the given volume, and the higher the strength, the better the gravels can transfer the shear wave than clay [39,40]. Hence, a greater referent shear strain appeared in the CGMs with the increase of gravel contents.…”
Section: Referent Shear Strainmentioning
confidence: 99%
“…A similar tendency was observed by Meidani et al [11,16,17], and it can be explained by the large size and the high strength of the gravels. Thelarger the size of the gravels, the less contacting points in the CGM at the given volume, and the higher the strength, the better the gravels can transfer the shear wave than clay [39,40]. Hence, a greater referent shear strain appeared in the CGMs with the increase of gravel contents.…”
Section: Referent Shear Strainmentioning
confidence: 99%
“…Due to various adverse factors, such as pounding and impact [49], chloride diffusion [50] and corrosion [51,52], and freeze and thaw [53,54], roadways are subject damages, such as potholes and cracks, which will negatively impact traffic flow [55], generating abnormal traffic patterns, such as sudden slow down and lane changes, which will worsen over time. Therefore, a spatiotemporal data mining approach by using the historical data will be developed.…”
Section: Identify Certain Roadway Damagesmentioning
confidence: 99%
“…Wang et al (2015) evaluated various properties of fresh cement-emulsified asphalt mortar and found that increasing the asphalt/cement ratio significantly reduced the compressive strength of the mortar. A further investigation of the properties of cement-stabilized gravel modified by emulsified asphalt (Wang et al, 2017) revealed that cement-emulsified asphalt-stabilized gravel with 5 wt% cement performed well both mechanically and in terms of frost resistance. And some recent studies show that surfactants also have a good effect on increasing the strength of cement asphalt emulsion mixture (Ouyang et al, 2018(Ouyang et al, , 2019Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 98%